Pengaruh Anti-VEGF pada Diabetic Retinopathy - Dicky Adrian (PT. Kalbe Farma Tbk., 2017)
Diabetic retinopathy adalah gangguan mata berupa perdarahan retina akibat komplikasi mikrovaskular diabetes, yang sifatnya kronis dan progresif. Diabetic retinopathy disebabkan peningkatan jumlah Advanced Glycation Endproducts (AGEs), aktivasi jalur polyol, aktivasi jalur stres oksidatif, peningkatan Vascular Endothelial Growth Factor (VEGF), dan peningkatan protein kinase-C. VEGF merupakan faktor kunci penyebab neovaskularisasi retina, dan terjadinya perdarahan retina. Anti VEGF dianggap dapat menurunkan progresifitas diabetic retinopathy. Anti VEGF dapat berupa antibodi terhadap reseptor VEGF atau VEGF itu sendiri, VEGF Trap Eye, dan aptamer VEGF.Diabetic retinopathy is a chronic and progressive retinal bleeding as a microvascular complication of diabetes. Diabetic retinopathy is caused by increased of Advanced Glycation Endproducts (AGEs), activation of polyol pathway, activation of oxidative stress pathway, increased of Vascular Endothelial Growth Factor (VEGF), and increased of protein kinase-C. VEGF is the key factor in retinal neovascularization and retinal hemorrhage. Anti-VEGF can reduce neovascularization, it can be an antibody to either VEGF or VEGF receptor, VEGF Trap-Eye, and VEGF aptamer.